A Study on the Impact of Management Accounting Application on the Management Efficiency of Public Hospitals in Thanh Hoa Province, Vietnam - DANG, Lan Anh; HONG, Le Thi; LE, Thi Minh Hue (Archives of Business Research, 2022)
Based on the actual situation of Public Hospitals in Thanh Hoa Province and the role of Management Accountants in performing the management function of managers, the authors conduct a study on the relationship between accounting application management to management efficiency in Public Hospitals in Thanh Hoa Province to find out the relationship between the application of management accounting to the operation management of the hospital, thereby making necessary recommendations for the application of Management Accounting. Management accounting in hospitals is reasonable and appropriate, bringing a positive impact on management in Public Hospitals in the current context of Financial Autonomy.